(untitled) (Mustansiria Dental Journal, 2018)
The maxillary sinus are pyramidal shaped cavities in the mid-facial aspect of the skull; they are bilateral structures, located beside each nasal fossa. Knowledge of the relationship between the root apex and the inferior wall of the maxillary sinus is crucial for diagnosis and treating a sinus pathosis as well as in assisting dental implantation, endodontic procedures and orthodontic treatment. Thirty patients attending Al-Ma’amoon dental centre were selected in this study according to a special criteria. Four digital periapical x –rays were taken for each patient using dental x – ray machine two views demonstrated both right and left permanent canines to measure the length of each tooth by direct double click technique, the other two views were taking with concentration on the apical area of each tooth, to measure the exact distance between the apex of the tooth and the floor of the maxillary sinus. Results of this study found that the distance between the apices of right permanent maxillary canines and the base of maxillary sinus was greater than that of left side and the distance between the canine apex and the floor of maxillary sinus increasing with increasing age.